Mapping the research trends of migration behavior in agricultural households: a bibliometric analysis - Saini, Sushmita; Burman, Rajarshi Roy; Padaria, Rabindra Nath; Mahra, Girijesh Singh; Bishnoi, Sitaram; Aditya, Kaustav; Nithyashree, M. L.; Mallick, Sonali; Mukherjee, Sweety; Padhan, Smruti Ranjan (Frontiers in Sustainable Food Systems, 2023)
The migration patterns of farmers, rural women, and youth within agricultural households have a significant impact on rural communities and the agricultural sector. To gain a deeper understanding of research trends in migration behavior, a study was conducted using comprehensive bibliometric analysis and text mining. René Descartes’ Discourse framework was employed to analyze 504 research articles retrieved from the Dimension.ai database followed by further analysis with Microsoft Excel, R software and VOS viewer. The study revealed a growing interest of various stakeholders in this field, with an increasing number of publications focusing on various aspects from 1934 to 2023. In terms of the publication’s performance analysis, the study identified human society and the second Sustainable Development Goal (SDG) as the most significant research areas. These areas aim to address hunger and improve food security for migrants. Regarding migration studies, three influential journals—Sustainability, World Development, and Journal of Rural Studies—were identified, with the most influential author being J. Vernon Henderson from the United Kingdom. Citation analysis was conducted to determine the highest number of citations for the influential author (J. V. Hernderon), journal (World Development), organization (World Bank), and country (United States) based on scientific attribution. Additionally, a co-word analysis was performed to research article’s abstracts to map into key thematic clusters that include climate change, food insecurity, and the COVID-19 crisis. The study visualized the social network of authors, organizations, and countries involved in co-authorship analysis within the research field. Furthermore, a journal co-citation analysis was undertaken to reveal the intellectual structure of migration studies in the agricultural context. Text mining of the research documents uncovered both anticipated and unanticipated effects of migration on households. Consequently, these findings provide valuable insights into future research directions and evidence-based policy framing which will contribute to shielding agricultural households from unforeseen consequences of migration, benefiting researchers, policymakers, and practitioners in this arena.